Obelia bidentata Clark 1875 ... - Galea, Horia R.; Häussermann, Verena; Försterra, Günter (Zenodo, 2009)
Obelia bidentata Clark, 1875 (fig. 5G) Material examined. Stn. 8 – 23.02.2008, 26 m, A565: several stems, ca. 5 mm high, epizoic on Symplectoscyphus milneanus (d’Orbigny, 1846); A566: a small, sterile colony, epizoic on Synthecium robustum Nutting, 1904; A580 (MHNG INVE 62830): a few sterile stems, epizoic on S. milneanus. Type locality. Long Island, Atlantic coast of the United States of America. Remarks. For a description of this well-known species, I refer to Cornelius (1995). World distribution. Likely cosmopolitan. For a detailed list of world records, see Medel & Vervoort (2000). Peña Cantero (2008) gave its distribution in the Antarctic and sub-Antarctic waters. Records from Chile. Gente Grande and Paso Ancho, Strait of Magellan (Orejas, unpublished results, see Pagès & Orejas 1999), South of Chiloé Island (present study). ... : Published as part of Galea, Horia R., Häussermann, Verena & Försterra, Günter, 2009, New additions to the hydroids (Cnidaria: Hydrozoa) from the fjords region of southern Chile, pp. 1-28 in Zootaxa 2019 on pages 23-24, DOI: 10.5281/zenodo.186052 ...